Viewpoint Non-Myths About Programming. - Ben-Ari, Mordechai (Communications of the ACM, 2011)
The article seeks to refute several common objections young people have about a career in computer science that, while perhaps true on a personal basis, are less persuasive when viewed within a larger context. The author points out the computer programming is no more boring than any other profession that has been mastered over the course of years. He further notes that spending hours each day looking at a screen is not a valid objection to a career in computer science, since people in many other careers do the same thing.